2010
DOI: 10.1111/j.1365-2559.2010.03556.x
|View full text |Cite
|
Sign up to set email alerts
|

ILK expression in human basal cell carcinoma correlates with epithelial–mesenchymal transition markers and tumour invasion

Abstract: ILK overexpression in BCC is implicated in tumour progression probably through the induction of an EMT-related molecular profile. Nuclear localization of E-cadherin in BCC is also associated with aggressive tumour features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 46 publications
(138 reference statements)
3
31
0
3
Order By: Relevance
“…Cytoplasmic and nuclear expression, when observed, was evaluated separately. Immunoreactivity was scored on a scale of 0-3 according to intensity of staining and percentage of positive cells as previously described (18). Staining intensity was graded as 0 (negative), 1 (weak), 2 (moderate), and 3 (strong).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Cytoplasmic and nuclear expression, when observed, was evaluated separately. Immunoreactivity was scored on a scale of 0-3 according to intensity of staining and percentage of positive cells as previously described (18). Staining intensity was graded as 0 (negative), 1 (weak), 2 (moderate), and 3 (strong).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…[13][14][15] Increased snail and decreased E-cadherin are involved in the progression of cancer and the shortening of survival. 12,16 In the present study, we assessed the snail-positive rate of NSCs and cancer cells that show glandular lumen in each section, and we found that snail-positive rate was significantly greater in NSCs than in cancer cells that show glandular lumen. In addition, the snail-positive rate in NSCs was greater than that in cancer cells that show glandular lumen in all patients (in all patients, [snailpositive rate in NSCs] ≧ [snail-positive rate in cancer cells that show glandular lumen]).…”
Section: Discussionmentioning
confidence: 83%
“…Twistl may be a feasible biomarker for highly invasive and/or metastatic BCC. The expression levels of Snail, the other transcription factor promoting EMT, have been shown to correlate with the depth of tumour invasion in BCC (8). However, no significant relationship was found between Snail and down-regulation of E-cadherin (8), suggesting that another transcription factor is involved in the regulation of EMT in BCC.…”
Section: Discussionmentioning
confidence: 98%
“…The expression levels of Snail, the other transcription factor promoting EMT, have been shown to correlate with the depth of tumour invasion in BCC (8). However, no significant relationship was found between Snail and down-regulation of E-cadherin (8), suggesting that another transcription factor is involved in the regulation of EMT in BCC. Our finding is in accordance with the notion that Twistl is capable of promoting EMT, contributing to aggressive invasion and multiple organ métastases.…”
Section: Discussionmentioning
confidence: 98%